Use of macroporous gelatine spheres as a biodegradable scaffold for guided tissue regeneration of healthy dermis in humans: An in vivo study - Huss, Fredrik R.M.; Nyman, Erika; Bolin, Johanna S.C.; Kratz, Gunnar (Journal of plastic, reconstructive & aesthetic surgery, 2010)
If a biodegradable scaffold is applied, the dermis can be regenerated by guided tissue regeneration. Scaffolds can stimulate in-growth of cells from the surroundings that migrate into them and start to produce autologous extracellular matrix as the scaffold is degraded. Several materials are available, but most of them are in the form of sheets and need to be laid on an open wound surface. A number of injectable fillers have been developed to correct soft-tissue defects. However, none of these has been used for guided tissue regeneration. We present a new technique that could possibly be used to correct dermal defects by using macroporous gelatine spheres as a biodegradable scaffold for guided tissue regeneration. In eight healthy volunteers, intradermal injections of macroporous gelatine spheres were compared with injections of saline and hyaluronic acid (Restylane ®). Full-thickness skin biopsy specimens of the implants and surrounding tissue were removed 2, 8, 12 and 26 weeks after injection, and the (immuno)histological results were analysed. The Restylane ® merely occupied space. It shattered the dermal tissue and compressed collagen fibres and cells at the interface between the implant and the dermis. No regeneration of tissue was found with this material at any time. The macroporous gelatine spheres were populated with fibroblasts already after 2 weeks. After 8 weeks the spheres were completely populated by fibroblasts producing dermal tissue. After 12 and 26 weeks, the gelatine spheres had been more or less completely resorbed and replaced by vascularised neodermis. There were no signs of capsular formation, rejection or adverse events in any subject. Further in vivo studies in humans are needed to evaluate the effect of the macroporous spheres fully as a matrix for guided tissue regeneration with and without cellular pre-seeding. However, the results of this study indicate the possibility of using macroporous gelatine spheres as an injectable, three-dimensional, degradable matrix for guided tissue regeneration.